Functional Gene Analysis Reveals Cell Cycle Changes and Inflammation in Endothelial Cells Irradiated with a Single X-ray Dose - Baselet, Bjorn; Belmans, Niels; Coninx, Emma; Lowe, Donna; Janssen, Ann; Michaux, Arlette; Tabury, Kevin; Raj, Kenneth; Quintens, Roel; Benotmane, Mohammed A.; Baatout, Sarah; Sonveaux, Pierre; et al. (Frontiers in Pharmacology, 2017)
Background and Purpose. Epidemiological data suggests an excess risk of cardiovascular disease (CVD) at low doses (0.05 and 0.1 Gy) of ionizing radiation (IR). Furthermore, the underlying biological and molecular mechanisms of radiation-induced CVD are still unclear. Because damage to the endothelium could be critical in IR-related CVD, this study aimed to identify the effects of radiation on immortalized endothelial cells in the context of atherosclerosis. Material and Methods. Microarrays and RT-qPCR were used to compare the response of endothelial cells irradiated with a single X-ray dose (0.05, 0.1, 0.5, 2 Gy) measured after various post-irradiation (repair) times (1 day, 7 days, 14 days). To consolidate and mechanistically support the endothelial cell response to X-ray exposure identified via microarray analysis, DNA repair signaling (γH2AX/53BP1-foci quantification), cell cycle progression (BrdU/7AAD flow cytometric analysis), cellular senescence (β-galactosidase assay with CPRG and IGFBP7 quantification) and pro-inflammatory status (IL6 and CCL2) was assessed. Results. Microarray results indicated persistent changes in cell cycle progression and inflammation. Cells underwent G1 arrest in a dose-dependent manner after high doses (0.5 and 2 Gy), which was compensated by increased proliferation after one week and almost normalized after two weeks. However, at this point irradiated cells showed an increased -Gal activity and IGFBP7 secretion, indicative of premature senescence. The production of pro-inflammatory cytokines IL6 and CCL2 was increased at early time points. Conclusions. IR induces pro-atherosclerotic processes in endothelial cells in a dose-dependent manner. These findings give an incentive for further research on the shape of the dose-response curve, as we show that even low doses of IR can induce premature endothelial senescence at later time points. Furthermore, our findings on the time- and dose dependent response regarding differentially expressed genes, cell cycle progression, inflammation and senescence show novel insights into the underlying molecular mechanisms of the endothelial response to X-ray radiation. This may in turn lead to the development of risk reducing strategies to prevent IR-induced CVD, such as the use of cell cycle modulators and anti-inflammatory drugs as radioprotectors and/or radiation mitigators.